Optimizing Multivessel PCI with Limited Stents: Successful Revascularization Without Left Main Intervention - Laksono, Sidhi; Putri Nurbaeti (Alami Journal (Alauddin Islamic Medical) Journal, 2026)
Background: Acute coronary syndrome (ACS) is a major cause of hospitalization andmortality. Patients with multivessel disease (MVD), especially with left main (LM)involvement, face higher risks of complications and adverse outcomes.Objective: A 55-year-old male with uncontrolled hypertension and diabetes presentedwith 16-hour chest pain. The ECG showed T-wave inversion in leads I and aVL, witha high-sensitivity troponin level of 59,480 ng/dL. He was diagnosed with high-risklateral NSTEMI.Methods: This is a case report. Coronary angiography (CAG) revealed 70% distal LMstenosis, 80% ostial stenosis with chronic total occlusion (CTO) in the proximal leftanterior descending (LAD) artery, and 80% subtotal occlusion in the left circumflex(LCx) artery. PCI was performed using drug-eluting stents in the LAD and LCx.Results: TIMI 3 flow was achieved without major complications. LM PCI was deferreddue to strategic stenting in the LAD and LCx, which improved perfusion andpotentially reduced the functional significance of LM stenosis.Conclusion: This case highlights the complexity of MVD PCI and demonstrates thattargeted stenting can optimize revascularization while minimizing procedural risks.Careful post-PCI assessment is essential for long-term management.